Pectin–Zeolite-Based Wound Dressings with Controlled Albumin Release - Kocaaga, Banu; Kurkcuoglu, Ozge; Tatlier, Melkon; Dinler-Doganay, Gizem; Batirel, Saime; Güner, Fatma Seniha (MDPI AG, 2022)
Hypoalbuminemia can lead to poor and delayed wound healing, while it is also associated with acute myocardial infarction, heart failure, malignancies, and COVID-19. In elective surgery, patients with low albumin have high risks of postoperative wound complications. Here, we propose a novel cost-effective wound dressing material based on low-methoxy pectin and NaA-zeolite particles with controlled albumin release properties. We focused on both albumin adsorption and release phenomena for wounds with excess exudate. Firstly, we investigated albumin dynamics and calculated electrostatic surfaces at experimental pH values in water by using molecular dynamics methods. Then, we studied in detail pectin–zeolite hydrogels with both adsorption and diffusion into membrane methods using different pH values and albumin concentrations. To understand if uploaded albumin molecules preserved their secondary conformation in different formulations, we monitored the effect of pH and albumin concentration on the conformational changes in albumin after it was released from the hydrogels by using CD-UV spectroscopy analyses. Our results indicate that at pH 6.4, BSA-containing films preserved the protein’s folded structure while the protein was being released to the external buffer solutions. In vitro wound healing assay indicated that albumin-loaded hydrogels showed no toxic effects on the fibroblast cells.
Keywords: Zeolite; Albumin; Wound dressing; Pectin; Article; pectin; wound dressing; zeolite; albumin